The Writing Effective Sentences for Students of SMP Negeri 6 Siak Hulu: Writing Effective Sentences - Yuliawan, Tri; Shomary, Sudirman; Sugara, Hendry; Nurlita, Anggun; Mahardika, Fajar ; Ayuni Syahira, Tasya (UIR Press, 2025)
Junior High School students must have the ability to write effective sentences. However, students' low ability to construct sentences that are in accordance with Indonesian language rules is often an obstacle in the learning process. Therefore, effective sentence writing training is intended as a form of community service and to improve students' literacy skills. This training uses an interactive approach to provide an understanding of basic concepts, group discussions to improve understanding, and direct writing practice. This is done with the aim of applying theory to written work. Activities are carried out in stages, starting with an explanation of effective sentence structures, finding common errors, and students revising their own work with guidance. The results of the training showed that students were better at writing sentences that were in accordance with the principles of clarity, accuracy, and unity of ideas. Students were also more confident in writing and understood the importance of good sentence structure for written communication. It is hoped that this training will have a positive impact in the long term on improving the literacy skills of junior high school students. In conclusion, this training contributes to improving student literacy, which is expected to have a positive impact on students' overall academic abilities.